A CRITICAL ANALYSIS OF KHWAJA GHULAM SAIYIDAIN’S PHILOSOPHY OF EDUCATION (International Journal of Food and Nutritional Sciences, 2022)
This research study is an attempt to explore the educational philosophy of the most reputed educational expert and policy maker of India Khwaja Ghulam Saiyidain. He was a distinguished Indian educationist, a visionary philosopher and a certified educational expert who made a significant and commendable contribution to India's educational system. He was constantly in the lead when it came to planning education and developing educational ideas, and he had a specific enthusiasm for Indian education. K.G. Saiyidain put forth the foundational ideas for Indian education and worked tirelessly to make it accessible to everyone. He was concerned about India's future, and he found the educational challenges to be a significant obstacle. He provided helpful suggestions for improving the educational system and gave convenient advice for the advancement of the education system and outlined a new education system. He successfully established the educational standards and changed them by putting all of his efforts and educational ideas into practise from the beginning. He was interested in a variety of domains of knowledge, including adult education, education in rural areas, education for women, social and moral education, innovative learning environment in schools, and education and discipline. In addition, he was deeply fond of John Dewey’s pragmatism besides being an idealist. He was a noted educational thinker and expert of international reputation. His idea of public education, which is so comprehensive as a whole that it serves as the foundation of universal humanism.